Calcium-fortification of potato chips - Deniega, Maricel Besana
ABSTRACT The main objective of the study was to fortify an acceptable potato chip with an optimum level of calcium using calcium lactate as fortificant. The recipe used in the preliminary studies was adopted from Arceo (1994), which was further improved to increase acceptability of its sensory characteristics to the consumers. Improvements done on the recipe included the following: boiling of potatoes in water instead of cooking them in a pressure cooker, flattening of the dough into a thinner sheet to improve texture, shortening of drying and frying times of the product to avoid over drying and overcooking and lessening the amount of pepper added into the recipe. Modifications were done based on recommendations and comments of the panelists. From an original rating of like slightly, the product's overall acceptability was increased to like moderately. Phase I dealt the fortification of the product with an optimum level of calcium lactate. The improved recipe was incorporates with various levels of calcium and subjected to sensory evaluation. Production, sensory evaluation and statistical analysis were repeated until an acceptable, optimum level of calcium in potato chips was established. Results from Preference and Descriptive Tests showed that the recipe fortified with 371 mg calcium was the most acceptable among all the formulations. Therefore, it was considered that the most acceptable, optimum level of calcium to be incorporated in 100g serving portion of the final product is 371 mg or 2.85g calcium lactate.This level was also chosen to be incorporated in the formulation that was standardized. Phase II dealt with the standardization of calcium-fortified product. The entire tests samples with like moderately ratings were found to have no significant difference using Analysis of Variance (ANOVA) at 5% level of significance. The three samples had the following physicochemical characteristics, microbiological characteristics and calcium content: pH- 5.8, 6.2 and 6.0; color- 5YR 7/10, 5YR 7/8 and 5YR 6/10 corresponding to orange color; %moisture(dry basis)- 5.26%, 6.45% and 5.84%; Total Aerobic Count (TAC),cfu/g- 800, 400 and 900; Yeast and Mold Count (YMC), cfu/g- 30, 90 and 18; Calcium content (mg/100g sample)- 423, 352 and 398. The study showed that calcium-fortified potato chip product is acceptable to the consumers and is relatively stable under several production runs of the standard formulation and procedure.